IMMEDIATE EARTHQUAKE PRECURSORS IN NEAR-GROUND ATMOSPHERIC ELECTRICITY - Rulenko O.P. (My University, 2001)
The subject of this paper is the little known anomalous change in the electrical characteristics of the near-ground atmosphere arising a few tens of hours to a few hours before earthquakes. Observations of electric-intensity and vertical current-density anomalies were summarized and analyzed for various seismic regions of the world. It was found for the first time that these anomalies, like many other earthquake precursors, were due to strain processes and that there were two mechanisms responsible for these two types of anomalies. These mechanisms are examined in detail in this paper.